Elastic modulus of cetacean auditory ossicles - Tubelli, A.; Zosuls, A.; Ketten, Darlene; Mountain, D. (John Wiley & Sons, Inc., 2014)
In order to model the hearing capabilities of marine mammals (cetaceans),it is necessary to understand the mechanical properties, such aselastic modulus, of the middle ear bones in these species. Biologically realisticmodels can be used to investigate the biomechanics of hearing in cetaceans,much of which is currently unknown. In the present study, theelastic moduli of the auditory ossicles (malleus, incus, and stapes) of eightspecies of cetacean, two baleen whales (mysticete) and six toothed whales(odontocete), were measured using nanoindentation. The two groups ofmysticete ossicles overall had lower average elastic moduli (35.2613.3GPa and 31.666.5 GPa) than the groups of odontocete ossicles (53.367.2GPa to 62.364.7 GPa). Interior bone generally had a higher modulus thancortical bone by up to 36%. The effects of freezing and formalin-fixation onelastic modulus were also investigated, although samples were few and noclear trend could be discerned. The high elastic modulus of the ossicles andthe differences in the elastic moduli between mysticetes and odontocetes arelikely specializations in the bone for underwater hearing. Anat Rec, 297:892–900, 2014. VC 2014Wiley Periodicals, Inc.